COLLABORATIVE DIALOGUE WRITING THROUGH PICTURE PROMPTS TO INCREASE THE STUDENTS’ WRITING SKILLS - Atika - Puspasari; Rosmaidar - -; Komala Dwi Syaputri (HOLISTICS, 2018)
Writing skills are predictors of academic success and are required for being able to participate in the global community and economy. Even so, the frequency of writing activities for students in secondary schools and even in higher education is still low. This is reflected in the students' inability to express their thoughts into writing. This paper discusses the method of writing collaborative dialogue as one of the efforts to improve students 'writing skills. It aims to prove whether the learning model of writing collaborative dialogue activities through images can improve students' writing skills and whether through this activity they are able to produce more writing ideas. The quasi-experimental method  design was used in this study. The data was collected by means of writing test. The results of the test were analyzed by the experienced rater in the teaching of writing. To calculate and compare means and standard deviations from both groups of students, SPSS was used.